[tex]1)\\\\2a+3b-c-4a-3b= -2a-c\\\\2)\\\\3x-2y+3,5x-y+2+0,5y=6,5x-2,5y+2\\\\3)\\\\x^2+2xy-3y^2-2x^2-2xy=-x^2-3y^2[/tex]
[tex]4)\\\\ \frac{1}{6}t^2+ \frac{1}{3} k^2t+ \frac{1}{3}tk^2-k^2t+ \frac{1}{2}t^2=\frac{1}{6}t^2+ \frac{2}{3} k^2t+ -k^2t+ \frac{3}{6}t^2=\frac{4}{6}t^2-\frac{1}{3}k^2t=\\\\=\frac{2}{3}t^2-\frac{1}{3}k^2t \\\\5)\\\\3x^2-2y^2-6x^2-2y^2=-3x^2-4y^2\\\\\text{Jednomianami podobnymi nazywamy jednomiany,}\\\text{ w\ ktorych wystepuja takie same czynniki literowe w tej samej potedze}\\\\odp.\ Jednomiany\ numer\ 3\ i\ 5 \ sa\ podobne .[/tex]